▼Eplerenone after myocardial infarction?. Issue 1 (2nd January 2008) - Unknown
Abstract : Each year in the UK, an estimated 50, 000 patients develop major left ventricular systolic dysfunction (LVSD) and heart failure following a myocardial infarct.1 Such patients have a particularly poor prognosis.2 ▼Eplerenone (Inspra – Pfizer) is an aldosterone-receptor antagonist for patients who have LVSD and heart failure following a recent myocardial infarct. Here, we discuss whether such patients should receive this drug.